Achieving sustainable development goals through organic agriculture empowering poor women to build the future. (Southeast Asia working papers., 2017)
Organic agriculture has been an attractive development strategy in achieving the Millennium Development Goals for developing countries, particularly owing to its low capital requirements. As evidenced in 11 studies financed by the Asian Development Bank Institute in 2005 to 2006, organic agricultural practices in selected Asian countries showed positive impacts on environment, biodiversity, and in particular on incomes and health for women farmers. In the Sustainable Development Goals era, organic agriculture remains relevant to help countries achieve their sustainable development goals.